CFD analysis of fouling effects on aerodynamics performance of turbine blades - Baheta, A.T. (Springer Verlag, 2019)
Fouling on gas turbine blades is detrimental to process operation as it may, over a period of time, reduce the blade efficiency and consequently the turbineâs efficiency. With the limitation of todayâs technology, experimental study or real-life observation of fouling in a gas turbine is beyond the imagination of maintenance engineers. Hence, the effect of fouling cannot be fully quantified for the engineers to come out with mitigation or intervention plans. Nevertheless, computational fluid dynamics (CFD) may provide a good simulation to understand the phenomena. In this chapter, a recent effort involving CFD study on the influence of fouling on the gas turbine performance is presented. Firstly, the nature of fouling on gas turbine and the general consequences are discussed. This is followed by an elaboration on how CFD study has been conducted by the authors. Finally, the findings from the study are discussed. Â© The Author(s), under exclusive licence to Springer Nature Singapore Pte Ltd. 2019.